Cardiac structure and function in young athletes - Shi, J. R. (2002)
The aim of the study was to examine the effects of a long-term endurance-training on resting and exercising cardiac responses on male adolescents. The sample consisted of 13 endurance-trained and 7 non-athletic male adolescents (x ± SE, age = 15.33 ± 0.33 and 15.15 ± 0.23 years, respectively). The volunteers underwent echocardiography at rest to determine left ventricular end diastole dimension (LVDd) and end systole dimension (LVDs), left ventricular posterior wall (PW), stroke volume (SV) and cardiac output (CO). On separate days, tests were conducted on a cycle ergometer to measure VO2max and anaerobic power, and skeletal muscle strength and endurance was determined on an isokinetic dynamometer. The relative peak oxygen uptake (VO2max ml/kg/min) was significantly higher (p < 0.05) in the endurance group (54.4 ± 1.8) than the control group (45.8 ± 1.6). The mean trial time was significantly longer in the endurance group (12.9 ± 0.7 minutes) than the control (10.4 ± 0.8 minutes; p < 0.05) and there was a significant relationship (r= 0.51; p < 0.05) between the length of test and peak oxygen uptake. No significant differences were noted between the two group in rest heart rate, peak heart rate, LVDd, LVDd/BSA, LVDs, LVDs/BSA, PW, PW/BSA, stroke volume (SV), SV indexed, cardiac output (CO) and CO indexed. The data indicate that endurance-trained male adolescents had higher value of maximal oxygen uptake than untrained male adolescents. The improvements in maximal oxygen uptake were associated with longer exercise time. Endurance-trained adolescents did not exhibit greater left ventricular internal dimension, left ventricular wall thickness, SV and CO at rest compared to the untrained. This observation suggests that endurance training stimulus need to be of greater intensity, duration and frequency in adolescent. In addition, the control group may have been engaged in sufficient exercise as to blur any differences that otherwise may have occurred. Furthermore, genetic factors may be more important in determining cardiovascular development and performance in adolescents, than was previously thought.